2009
DOI: 10.1007/s10267-008-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Constant association of ophiostomatoid fungi with the bark beetle Ips subelongatus invading Japanese larch logs

Abstract: Ceratocystiopsis, Ceratocystis, Grosmannia, and Ophiostoma species were isolated from Ips subelongatus and beetle-infested Japanese larch logs collected at several areas in central and northern Honshu Island, Japan, to determine constant associates of I. subelongatus. Ceratocystiopsis minuta, two species of Ceratocystis, three species of Grosmannia, and four species of Ophiostoma were isolated. Of the fungi isolated in the present study, G. laricis, O. brunneociliatum, and O. piceae were constant associates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Other than isolate (CMW 452, group B) that came from Pseudotsuga in the USA, all isolates in these five lineages originated from Picea. Both of the other species in the complex have been reported only from Japan, with G. laricis associated with I. subelongatus Motschulsky infesting larch (Van der Westhuizen et al 1995;Yamaoka et al 1998Yamaoka et al , 2009, and G. aenigmatica restricted to I. typographus f. japonicus on spruce (Jacobs et al 1998;Yamaoka et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Other than isolate (CMW 452, group B) that came from Pseudotsuga in the USA, all isolates in these five lineages originated from Picea. Both of the other species in the complex have been reported only from Japan, with G. laricis associated with I. subelongatus Motschulsky infesting larch (Van der Westhuizen et al 1995;Yamaoka et al 1998Yamaoka et al , 2009, and G. aenigmatica restricted to I. typographus f. japonicus on spruce (Jacobs et al 1998;Yamaoka et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…This species groups only peripherally to the hardwood and conifer clades of the O. piceae -complex ( Zipfel et al 2006 , Grobbelaar et al 2009 ), but based on morphology, resides within the complex ( Harrington et al 2001 ). Ophiostoma floccosum is widely distributed, but usually reported in low numbers associated with bark beetles primarily on pine trees ( Mathiesen 1951 , Harrington et al 2001 , de Beer et al 2003b , Jacobs et al 2003 , Kim et al 2007 , Lu et al 2009 , Yamaoka et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates in the present study came from Russia and mainly from I. typographus on spruce, but also from Pityogenes chalcographus , Tomicus minor and T. piniperda on pine. The fungus seems to be a constant associate on larch of I. cembrae in Europe and I. subelongatus in Japan ( Yamaoka et al 2009 ) and was shown to be only mildly pathogenic to its host trees ( Lieutier et al 1989 , Yamaoka et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…4, 5, Wang et al 2019). Ceratocystiopsis minuta and O. brunneo-ciliatum were reported as present in both Europe and Japan (Aoshima 1965;Redfern et al 1987;Redfern 1989;Yamaoka et al 1998Yamaoka et al , 2009Kirisits et al 2000;Stauffer et al 2001;Kirisits 2004;Jankowiak et al 2007;Jankowiak et al 2017;Yamaoka 2017); however, the reports of their existence in Japan also relied only on morphological identification, and would require molecular confirmation. This is particularly pertinent for O. brunneo-ciliatum, which is one of more frequently reported species associated with I. subelongatus in Japan (Aoshima 1965;Yamaoka et al 1998Yamaoka et al , 2009Yamaoka 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The ophiostomatoid fungi associated with I. subelongatus in Japan have been investigated systematically by Aoshima (1965), Westhuizen et al (1995), Yamaoka et al (1998, Yamaoka et al 2009, Chung et al (2006), Masuya et al (2009) and Ando et al (2016). Yamaoka (2017) has summarized the taxonomic knowledge of these fungi in Japan, where at least 12 species were reported to be associated with I. subelongatus, including five species of Ophiostoma, three of Grosmannia, two of Endoconidiophora, and one of Ceratocystiopsis and Graphilbum (Additional file 1: Table S1).…”
Section: Introductionmentioning
confidence: 99%